2017
DOI: 10.1017/s1751731116001774
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian inference of genetic parameters for ultrasound scanning traits of Kivircik lambs

Abstract: Ultrasound scanning traits have been adapted in selection programs in many countries to improve carcass traits for lean meat production. As the genetic parameters of the traits interested are important for breeding programs, the estimation of these parameters was aimed at the present investigation. The estimated parameters were direct and maternal heritability as well as genetic correlations between the studied traits. The traits were backfat thickness (BFT), skin + backfat thickness (SBFT), eye muscle depth (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Previous studies on different cattle breeds (Nellore, Red Angus, and Piedmontese) reported values for the REA ranging from 0.21 to 0.26 ( Boldt et al, 2018 ; Savoia et al, 2019 ). In 2007, rib eye muscle depth heritability of Kivircik lambs was estimated using Bayesian inference as 0.23 ( Cemal et al, 2016 ). Our results of the heritability of the REA are also similar to those of a previous report (0.23) ( Pollott and Greeff, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on different cattle breeds (Nellore, Red Angus, and Piedmontese) reported values for the REA ranging from 0.21 to 0.26 ( Boldt et al, 2018 ; Savoia et al, 2019 ). In 2007, rib eye muscle depth heritability of Kivircik lambs was estimated using Bayesian inference as 0.23 ( Cemal et al, 2016 ). Our results of the heritability of the REA are also similar to those of a previous report (0.23) ( Pollott and Greeff, 2004 ).…”
Section: Discussionmentioning
confidence: 99%
“…Goat breeding is typically conducted in regions where agricultural cultivation and other forms of animal husbandry are not viable, particularly in the inner-forest areas. Hair goats, which constitute 97.8 % of Türkiye's goat population and for which many studies have been carried out to define their produc-tivity characteristics, are mostly raised in the mountainous regions of Türkiye (Simsek et al, 2007;Atay et al, 2010;Cemal et al, 2019;Sirin, 2019;TUIK, 2022;Cemal et al, 2021). Although Hair goats are bred in all regions of Türkiye, they are known for their resilience to severe climatic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Data collected from agricultural experiments have been analyzed using different statistical methods, such as analysis of variance, maximum likelihood, REML and Bayesian methods. Despite a great number of literatures on the design and analysis of agricultural field experiments, dating back to the early 1900s, and a large uptake of Bayesian methods in many other scientific fields in the last 30 years (Firat, et al, 1997a;Firat, et al, 1997b;Firat, 2001;Karaman, et al, 2014;Cemal, et al, 2016;Firat et al, 2016), Bayesian analysis for agricultural field experiments has not received very much attention. Statistical methods for the design and analysis of agricultural field experiments were essentially developed by R. A. Fisher, F. Yates and many others.…”
Section: Introductionmentioning
confidence: 99%